Impactos da utilização da nota fiscal eletrônica nas atividades de monitoramento e fiscalização do ICMS: um estudo na Secretaria da Fazenda do Estado do Ceará - Sousa, Jucélio Praciano Rodrigues de (2010)
Since 2008, tax administrations have to face serious challenges in adapting the procedures of monitoring and inspecting taxes, given the use of the Electronic Invoice by taxpayers, as an adaptation process of business transactions by electronic media. The Electronic Invoice is a national model, as guaranteed by the legal validity of digital signature of the sender, reducing expenses at the reception, typing and storage and, at the same time, allowing a real-time monitoring of business operations by entities responsible for the collection of taxes. The general objective of this work is to analyze how the use of the Electronic Invoice impacted the activities of monitoring and supervising ICMS (Goods and Service Tax) in Finance Secretary of the State of Ceará. In order to aim this objective, firstly we attempted to identify changes in the activities of monitoring and inspecting ICMS (Goods and Service Tax) referring to the monitored period, inspection attendance, the use of sampling and the procedure for a conference on values, quantities or balances according to the Electronic Invoice, and later, changes in surveillance and monitoring activities related to the regularity of the registration status of the taxpayer and the steps to collect economic and fiscal information from the Electronic Invoice. To substantiate this theoretical study was conducted to review the literature addressing the issues raising in the context of public administration and information technology and e-government. The methodology used in this research was to study the unique case in the Ministry of Finance of the State of Ceará, FROM where information was collected about the activities of monitoring and inspecting ICMS, starting from the introduction of Electronic Invoice. The results indicate that there were impacts arising from the use of electronic invoices in the activities of monitoring and inspecting ICMS (Goods and Service Tax) in the Finance Secretary of the State of Ceará, in the following aspects: the monitoring of commercial operations will focus on the events in the present, the , inspection attendance was replaced by a remote monitoring, the use of total surveillance was replaced by the sampling technique, the procedures for manual verification were substituted for electronic media, improving speed in the early identification of invoices issued by or destined to written off or inactive taxpayers, and faster procedures for collection of economic and fiscal information.